Pancreatic Cancer - Riess, H.; Goerke, A.; Oettle, H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Although pancreatic cancer is one of the most serious forms of cancers, the outlook for patients could be improved. The lack of clinical symptoms of early, surgically removable disease most often limits curative treatment options. The aggressive tumor cell biology, leading to a locally advanced nature of the disease and to early metastases, allows curative resection in only 20% of patients at the time of diagnosis. This book gives insight into the current understanding of the management of pancreatic cancer and considers recent findings in cancer research. It provides answers to questions of how to know when cancer is respectable, how to proceed when the diagnosis comes too late for a curative approach, and how to assess different study results. Moreover, it highlights new upcoming therapeutic options and experimental approaches, which might further improve the future prospects for patients with pancreatic adenocarcinoma.
Pancreatic Cancer: Step by Step Forward -- Pancreatic Cancer: Step by Step Forward -- Diagnosis -- CT and MR Imaging of Pancreatic Cancer -- Nuclear Medical Methods for the Diagnosis of Pancreatic Cancer: Positron Emission Tomography -- Therapy and Monitoring of Disease -- Surgical Techniques for Resectable Pancreatic Cancer -- Postoperative Staging of Pancreatic Cancer -- Adjuvant Therapy in Patients with Pancreatic Cancer -- First-Line Chemotherapy in Advanced Pancreatic Cancer -- Second-Line Chemotherapy in Advanced Pancreatic Cancer -- Neoadjuvant and Adjuvant Strategies for Chemoradiation -- Primary Advanced Unresectable Pancreatic Cancer -- Brachytherapy of Liver Metastases -- Detection of Disease Recurrence and Monitoring of Therapy -- Surgical Palliation of Advanced Pancreatic Cancer -- New Treatment Strategies and Outlook -- Antiangiogenic Strategies in Pancreatic Cancer -- Targeted Therapy of the Epidermal Growth Factor Receptor in the Treatment of Pancreatic Cancer -- Antisense Therapeutics for Tumor Treatment: The TGF-beta2 Inhibitor AP 12009 in Clinical Development Against Malignant Tumors -- NF-? B as a Molecular Target in the Therapy of Pancreatic Carcinoma -- Immunotherapeutic Approaches in Pancreatic Cancer -- Src Kinase and Pancreatic Cancer.
Keywords: Oncology .; Gastroenterology .; Oncology; Gastroenterology